Land use changes of the riparian landscape in Hungary between 1990 and 2018 - Erdei, Tímea; Boromisza, Zsombor; Domokos, Endre (Acta Geographica Debrecina Landscape & Environment series, 2022)
The protection and the restoration of rivers is one of the most important challenges of our time, due to the impact of human activities. The aim of the research was to assess the land use changes in the Hungarian riparian landscape. Several landscape corridors of different (50-100-300-500 m) widths near rivers were analyzed since 1990, using the CORINE Land Cover database. Positive changes in the land use of riparian landscape can be seen: continuous increase in the case of forest areas; and slight decrease in the extent of agricultural land since 1990. Unfortunately, the extent of grasslands and other near-natural areas is reduced; and there has been a steady increase in built-up areas. Examining the changes in built-up areas in more detail, a big increase is shown by the extent of urban green areas. As a continuation of the research, an evaluation methodology is being developed to determine the restoration potential of urban rivers on study area level and on national level. The results presented in this paper on land use changes and land use conditions can be useful for the research about restoration potential at national level.